Transforming organizational culture in higher education: a strategic change management case study for higher learning institutions using the IRACE framework - Twabu, Khanyisile Yanela (Frontiers in Education, 2025)
Higher education institutions (HEIs) worldwide face mounting pressures to transform their organizational cultures in response to the Fourth Industrial Revolution (4IR), socio-political imperatives, and evolving expectations from diverse stakeholders. This transformation process is especially critical in African contexts, where universities must simultaneously pursue global competitiveness and address historical inequities through decolonization, Africanisation, and inclusive governance. This paper presents the IRACE Framework: Initiate, Reflect, Act, Consolidate, Evaluate, as a strategically aligned and context-sensitive model for cultural transformation in HEIs. By synthesizing established change management models (Lewin’s Three-Step Model, Kotter’s Eight-Step Model, Prosci’s ADKAR, the PREXSU model, and the TIPS™ Managerial Leadership Framework) with governance principles from King IV, the IRACE Framework integrates human and systemic dimensions of change. The University of South Africa (UNISA) serves as the focal case to illustrate the framework’s design and application, providing insight into stakeholder engagement, governance alignment, and the embedding of transformation in institutional priorities. Findings indicate that successful culture transformation in HEIs requires structured yet adaptive processes, participatory design, robust governance integration, and capacity building. The paper concludes with recommendations for HEI leaders, policy-makers, and researchers seeking sustainable and ethically grounded change strategies.